2017
DOI: 10.1002/pssr.201700275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Y Dopant on Lattice Distortion and Electrical Properties of In3SbTe2 Phase‐Change Material

Abstract: Using a computational high‐throughput screening method, 29 doping elements have been investigated for improving the thermal and electrical characteristics of In3SbTe2 (IST) phase‐change material. Among the 29 dopants, it is found that Y offers largest distortion in the lattice structure of IST with negative doping formation energy while Y substitutes the In site. The atomic lattice images clearly show that the In site is substituted by Y and the distortion angles of the Y‐doped IST (Y‐IST) are well matched wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The models of InSb/a-Bi and InTe/a-Bi consist of In 32 Sb 32 Bi 64 and In 20 Te 20 Bi 35 , respectively. In our previous work, 26 the effect of the change in system size on the energy parameters such as doping formation energy was verified; moreover, the reliability of a 2 × 2 × 2 supercell (64 atoms) of IST for doping modeling was tested via a comparison with a 3 × 3 × 3 one (216 atoms). 26,59 The energy difference was less than 0.1 eV.…”
Section: ■ Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…The models of InSb/a-Bi and InTe/a-Bi consist of In 32 Sb 32 Bi 64 and In 20 Te 20 Bi 35 , respectively. In our previous work, 26 the effect of the change in system size on the energy parameters such as doping formation energy was verified; moreover, the reliability of a 2 × 2 × 2 supercell (64 atoms) of IST for doping modeling was tested via a comparison with a 3 × 3 × 3 one (216 atoms). 26,59 The energy difference was less than 0.1 eV.…”
Section: ■ Methodsmentioning
confidence: 95%
“…In our previous works, it was observed that the set and reset switching speeds of PCRAMs fabricated using IST doped with Y and Bi elements (Y 12.38 (In 3 SbTe 2 ) 87.62 and Bi 5.5 (In 3 SbTe 2 ) 94.5 ) are evidently more effective than those of the devices fabricated with pure IST and GST. Such an improvement is strongly related to the effects of lattice distortion in the doped IST.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations